-2w-3w-(11-2w+10w-2)-(2-w-w)=4(-2w+6-2w-3)

Simple and best practice solution for -2w-3w-(11-2w+10w-2)-(2-w-w)=4(-2w+6-2w-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2w-3w-(11-2w+10w-2)-(2-w-w)=4(-2w+6-2w-3) equation:


Simplifying
-2w + -3w + -1(11 + -2w + 10w + -2) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)

Reorder the terms:
-2w + -3w + -1(11 + -2 + -2w + 10w) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)

Combine like terms: 11 + -2 = 9
-2w + -3w + -1(9 + -2w + 10w) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)

Combine like terms: -2w + 10w = 8w
-2w + -3w + -1(9 + 8w) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)
-2w + -3w + (9 * -1 + 8w * -1) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)
-2w + -3w + (-9 + -8w) + -1(2 + -1w + -1w) = 4(-2w + 6 + -2w + -3)

Combine like terms: -1w + -1w = -2w
-2w + -3w + -9 + -8w + -1(2 + -2w) = 4(-2w + 6 + -2w + -3)
-2w + -3w + -9 + -8w + (2 * -1 + -2w * -1) = 4(-2w + 6 + -2w + -3)
-2w + -3w + -9 + -8w + (-2 + 2w) = 4(-2w + 6 + -2w + -3)

Reorder the terms:
-9 + -2 + -2w + -3w + -8w + 2w = 4(-2w + 6 + -2w + -3)

Combine like terms: -9 + -2 = -11
-11 + -2w + -3w + -8w + 2w = 4(-2w + 6 + -2w + -3)

Combine like terms: -2w + -3w = -5w
-11 + -5w + -8w + 2w = 4(-2w + 6 + -2w + -3)

Combine like terms: -5w + -8w = -13w
-11 + -13w + 2w = 4(-2w + 6 + -2w + -3)

Combine like terms: -13w + 2w = -11w
-11 + -11w = 4(-2w + 6 + -2w + -3)

Reorder the terms:
-11 + -11w = 4(6 + -3 + -2w + -2w)

Combine like terms: 6 + -3 = 3
-11 + -11w = 4(3 + -2w + -2w)

Combine like terms: -2w + -2w = -4w
-11 + -11w = 4(3 + -4w)
-11 + -11w = (3 * 4 + -4w * 4)
-11 + -11w = (12 + -16w)

Solving
-11 + -11w = 12 + -16w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '16w' to each side of the equation.
-11 + -11w + 16w = 12 + -16w + 16w

Combine like terms: -11w + 16w = 5w
-11 + 5w = 12 + -16w + 16w

Combine like terms: -16w + 16w = 0
-11 + 5w = 12 + 0
-11 + 5w = 12

Add '11' to each side of the equation.
-11 + 11 + 5w = 12 + 11

Combine like terms: -11 + 11 = 0
0 + 5w = 12 + 11
5w = 12 + 11

Combine like terms: 12 + 11 = 23
5w = 23

Divide each side by '5'.
w = 4.6

Simplifying
w = 4.6

See similar equations:

| 6d=96 | | 18d+9=24d-63 | | 10k+13=4k+49 | | r+sx=m | | 5(7x-4)(4x+5)=0 | | 15d+82=34d-51 | | .10(m-100)+15+20=.5m+20+20 | | 3x+12x=10 | | 6q+44=7q+17 | | log(x+12)-logx=2 | | y=-4(12)-10 | | 3x+7=-x^2 | | 5r+91=29r-29 | | 112+8x=360 | | 33k^2+5k=0 | | 4x-97=x+65 | | 9(t-4)+6t=5(3t+5)-8 | | 2y+20=y | | 11m+79=46m-96 | | 2x-(3x)= | | (x+5)(4x-5)=0 | | 3x+7=3x-2 | | 17x-24=14x+18 | | a*x+b=3 | | (5-6i)(-2+4i)= | | =40x^3+2600x^2-40x | | 8j+16=15j-82 | | 3x(6)+2=5x-2 | | 3j=5j-6 | | 12s-89=3s+73 | | (7x+19)(2x-5)=0 | | (10-R)+(20-D)=0 |

Equations solver categories